Molecular Mechanisms of Topography Sensing by Osteoblasts: An Update - Pablo Rougerie; Rafaela Silva dos Santos; Marcos Farina; Karine Anselme (Applied Sciences, 2021)
Bone is a specialized tissue formed by different cell types and a multiscale, complex mineralized matrix. The architecture and the surface chemistry of this microenvironment can be factors of considerable influence on cell biology, and can affect cell proliferation, commitment to differentiation, gene expression, matrix production and/or composition. It has been shown that osteoblasts encounter natural motifs in vivo, with various topographies (shapes, sizes, organization), and that cell cultures on flat surfaces do not reflect the total potential of the tissue. Therefore, studies investigating the role of topographies on cell behavior are important in order to better understand the interaction between cells and surfaces, to improve osseointegration processes in vivo between tissues and biomaterials, and to find a better topographic surface to enhance bone repair. In this review, we evaluate the main available data about surface topographies, techniques for topographies’ production, mechanical signal transduction from surfaces to cells and the impact of cell–surface interactions on osteoblasts or preosteoblasts’ behavior.